Neuroregeneration: Spatial Differences in Cellular and Molecular Responses as a Function of the Material Used in Conduit‐Mediated Repair and Autograft Treatment of Peripheral Nerve Injuries (Adv. Funct. Mater. 12/2018). (25th March 2018) - Daly, William T.; Niemier, Ryan; Dillon, Simon T.; Wang, Huan; Mirsky, Rhona; Jessen, Kristjan; Windebank, Anthony; Pandit, Abhay
Abstract : The regenerative environment within different biomaterial nerve conduits remains poorly understood. In article number1702170, Abhay Pandit and co‐workers highlight the proteomic changes that occur spatially throughout both natural and synthetic biomaterial conduits compared to autografts. The study explores how different materials activate different biological functions during the early stages of regeneration and where they can be supplemented to enhance repair.